2007
DOI: 10.1093/nar/gkm601
|View full text |Cite
|
Sign up to set email alerts
|

Muscleblind-like 1 interacts with RNA hairpins in splicing target and pathogenic RNAs

Abstract: The MBNL and CELF proteins act antagonistically to control the alternative splicing of specific exons during mammalian postnatal development. This process is dysregulated in myotonic dystrophy because MBNL proteins are sequestered by (CUG)n and (CCUG)n RNAs expressed from mutant DMPK and ZNF9 genes, respectively. While these observations predict that MBNL proteins have a higher affinity for these pathogenic RNAs versus their normal splicing targets, we demonstrate that MBNL1 possesses comparably high affinitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
261
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(273 citation statements)
references
References 39 publications
10
261
2
Order By: Relevance
“…The loss of chloride channels in myotonic dystrophy is thought to be due to an accumulation of RNA with CUG or CCUG repeats in the nucleus that disrupt the function of RNA binding proteins, such as muscleblind-like 1 and 2; consequently, aberrantly spliced Clcn1 mRNA that contains exon 7a is degraded via nonsense-mediated decay (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). We tested for this mechanism in HD interosseous muscle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of chloride channels in myotonic dystrophy is thought to be due to an accumulation of RNA with CUG or CCUG repeats in the nucleus that disrupt the function of RNA binding proteins, such as muscleblind-like 1 and 2; consequently, aberrantly spliced Clcn1 mRNA that contains exon 7a is degraded via nonsense-mediated decay (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). We tested for this mechanism in HD interosseous muscle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In MD patients the sequestration of MBNL1 and other splicing factors by the mutant mRNAs leads to misregulated splicing, which is believed to be the underlying pathogenic mechanism in MD [34][35][36] . Similarly MBNL1 has been shown to bind CAG repeats 37,38 leading to dysregulated alternative splicing of target mRNAs in CAG repeat expansion disorders 39 . Furthermore, in a Drosophila model of MachadoJoseph disease, another CAG repeat expansion disorder, the MBNL1 protein enhanced CAG repeat RNA toxicity 8,[34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly MBNL1 has been shown to bind CAG repeats 37,38 leading to dysregulated alternative splicing of target mRNAs in CAG repeat expansion disorders 39 . Furthermore, in a Drosophila model of MachadoJoseph disease, another CAG repeat expansion disorder, the MBNL1 protein enhanced CAG repeat RNA toxicity 8,[34][35][36][37][38] . Thus, binding and sequestration of MBNL1 might be one possible mechanism contributing to RNA toxicity in CAG repeat expansion disorders (reviewed in Krzyzosiak et al 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that MBNL1 forms dimers and self-interactions are mediated by the C-terminal region (AA positions 239-382). 37 This region contains the described variant and it is possible that in this case dimerization and therefore gene function is impaired.…”
Section: Discussionmentioning
confidence: 99%